Can survival analyses detect hunting pressure in a highly connected species? Lessons from straw-coloured fruit bats. - Hayman DTS; Peel AJ (My University, 2016)
Animal behaviour, social structure and population dynamics affect community structure, interspecific interactions, and a species' resilience to harvesting. Building on new life history information for the straw-coloured fruit bat (Eidolon helvum) from multiple localities across Africa, we used survival analyses based on tooth-cementum annuli data to test alternative hypotheses relating to hunting pressure, demography and population connectivity. The estimated annual survival probability across Africa was high (≥ 0.64), but was greatest in colonies with the highest proportion of males. This difference in sex survival, along with age and sex capture biases and out-of-phase breeding across the species' distribution, leads us to hypothesize that E. helvum has a complex social structure. We found no evidence for additive mortality in heavily hunted populations, with most colonies having high survival with constant risk of mortality despite different hunting pressure. Given E. helvum's slow life history strategy, similar survival patterns and rate among colonies suggest that local movement and regional migration may compensate for local excess hunting, but these were also not clearly detected. Our study suggests that spatio-temporal data are necessary to appropriately assess the population dynamics and conservation status of this and other species with similar traits.
Keywords: Eidolon helvum; Demography; Hunting; Survival analyses; Bayesian population analyses; 05 Environmental Sciences; 06 Biological Sciences; 07 Agricultural and Veterinary Sciences